2014
DOI: 10.18357/ijcyfs.harta.532014
|View full text |Cite
|
Sign up to set email alerts
|

Resilience-Building With Disabled Children and Young People: A Review and Critique of the Academic Evidence Base

Abstract: The aim of this paper was to review published accounts of resilience-based approaches with and for disabled children and young people aged up to 25 years. The review is part of a broader study looking more generally at resilience-based interventions with and for young people. The authors attempt to summarise the approaches and techniques that might best support those children and young people who need them the most. However, when compared to the number of evaluated resilience-based approaches to working with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
(95 reference statements)
0
11
0
1
Order By: Relevance
“…It is generally acknowledged that children and adolescents with disabilities often encounter additional adversities, disadvantages, and difficulties during their development, and experience exclusion from age-appropriate activities (Hart et al, 2014). For this reason, it is suggested that interventions and practices aiming to enhance resilience may be particularly beneficial for these children, provided that their access to and equal participation in them are ensured (Hart et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally acknowledged that children and adolescents with disabilities often encounter additional adversities, disadvantages, and difficulties during their development, and experience exclusion from age-appropriate activities (Hart et al, 2014). For this reason, it is suggested that interventions and practices aiming to enhance resilience may be particularly beneficial for these children, provided that their access to and equal participation in them are ensured (Hart et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience refers to positive outcomes with regard to adaptation and development despite the presence of significant challenges (Masten & Coatsworth, 1995). It is considered to be a dynamic process resulting from the interactions both within the individual and between her and the environment (Hart et al, 2014;Luthar et al, 2000;Masten, 2001). Resilience implies the involvement of protective factors (Rutter, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience research that was conducted based on the perspectives of people with disabilities in general and those with blindness in particular are disappointingly lacking (Hart et al 2013 ). Luthar and Zelazo ( 2003 ) also indicated that one of the weaknesses of research on resilience has been the exclusive focus on children and adolescents without disability.…”
Section: Introductionmentioning
confidence: 99%
“…In this stressful situation, children with special needs are possibly having a lot of difficulties in following educational program and enhancing their academic, social and other life skills (Hart, Heaver, Brunnberg, Sandberg, Macpherson, Coombe, and Kourkoutas, 2014). The important aspect that makes some children with special needs succeed when faced with adversity or stressful condition is resilience -an ability to cope or bounce back from significant adverse life situations or stresses in such ways that are not only immediately effective, but also result in an increased ability to respond to future adversity.…”
Section: Introductionmentioning
confidence: 99%